THE SHIPPERâS LIABILITY UNDER THE REGULATION OF THE TRANSPORTATION MINISTER NO. 77 OF 2011 CONCERNING THE SHIPPERâS LIABILITY OF THE AIR FREIGHT - Adriani, Rhirien (Jurnal IUS, 2015)
Air transportation is one of the most desirable transportation because it offers various facilities and it takes relatively short time. In the fact, air freight deal with some obstacles for instances delays and/or cancellations. This, of course, is very detrimental to the passengers as the user of the air freight. In the transportation law, there are three kinds of liability principles, i.e. fault liability, presumption liability and strict liability. The implementation of the liability under the regulation of the transportation minister sets about compensation to passengers. The implementation of liability for flight delays and cancellations at Sultan Salahuddin Bima Airport has not been done maximally. The Weather and operational techniques are causative factor for the delays and cancellations. The regulation of the transportation minister provides set of rules which ensure justice for passengers of air transportation with strict liability principles.Keywords: liability, flight delays, flight cancellations